Hydrogel-Based Enzyme and Cofactor Co-Immobilization for Efficient Continuous Transamination in a Microbioreactor - Menegatti, Tadej; Žnidaršič-Plazl, Polona (Frontiers in Bioengineering and Biotechnology, 2021)
A microbioreactor was developed in which selected amine transaminase was immobilized together with the cofactor pyridoxal phosphate (PLP) to allow efficient continuous transamination. The enzyme and cofactor were retained in a porous copolymeric hydrogel matrix formed in a two-plate microreactor with an immobilization efficiency of over 97%. After 10 days of continuous operation, 92% of the initial productivity was retained and no leaching of PLP or enzyme from the hydrogel was observed. The microbioreactor with co-immobilized cofactor showed similar performance with and without the addition of exogenous PLP, suggesting that the addition of PLP is not required during the process. The space-time yield of the microbioreactor was 19.91 g L−1 h−1, while the highest achieved biocatalyst productivity was 5.4 mg mgenzyme−1 h−1. The immobilized enzyme also showed better stability over a wider pH and temperature range than the free enzyme. Considering the time and cost efficiency of the immobilization process and the possibility of capacity expansion, such a system is of great potential for industrial application.